Initiatives agricoles comme antiprojet d’un projet d’urbanistes - Ilaria Pasini; Alberto Minelli; André Fleury (Projets de Paysage)
Many agri-urban projects, planned by urban planners, do not consider the reality of modern agriculture, because they ignore the participation of farmers. This study tries to assess the feasibility of an agri-urban project, proposed by an Urban Planning Office of a French new town, Marne-la-Vallée, through the analysis of farmers strategies in the neighbourhood. In fact, these farmers have actually anticipated most planning questions with an innovating agriculture, they have drawn up some future guidelines of which.